ANALISIS STRUKTUR TEKS EKSPOSISI PADA KARYA SISWA KELAS X ADMINISTRASI PERKANTORAN SMK NEGERI 1 JAMBI - Nurfadillah Sugiarti; Sainil Amral; Sumiharti Sumiharti (Universitas Batanghari, 2018)
The purpose of this research is to describe the students ability in writing exposition text at class XAdministrasi Perkantoran 1 SMK Negeri 1 Kota Jambi Academic Year 2017/2018. This research is qualitative descriptive. The primary data of the research is students exposition text. The data is collected by using documentation technique. The sample is taken by using simple random sampling technique. The result of the research shows that there are 24 students who wrote exposition text by using good thesis structure, there are 27 students who wrote exposition text by using good sequences of argument, and there are 27 students who wrote exposition text by using good repetition. Based on the result of the research, it can be concluded that, in general, students ability in writing exposition text at class XAdministrasi Perkantoran 1 SMK Negeri 1falls into good criteria. Key Words: exposition text, texts structure